HUBUNGAN PENGETAHUAN DAN POLA ASUH ORANG TUA TERHADAP PERILAKU SEKS REMAJA DI SMAN 15 JAKARTA - Pertiwi, Nur Fitri Ayu; Munawarah, Raudhatul; Nurlaili, Helmi (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Great growth and development occurs during adolescence. This growth and development is not only physical, but also psychological and intellectual. This phase makes teenagers have a great sense of curiosity about developments that occur in themselves. This curiosity must receive special attention from the environment, especially parents. Parental parenting styles will influence adolescent development and will have an impact on their psychological development. The aim of this research is to determine the relationship between parental knowledge and parenting patterns on adolescent sexual behavior at SMAN 15 Jakarta. This type of quantitative research with a cross-sectional approach. The total sample was 94 people from the entire student population of SMAN 15 Jakarta using a simple random sampling technique. Analysis was carried out using Fisher's exact test. The results of the univariate analysis of teenagers at SMAN 15 Jakarta mostly had non-risky sexual behavior at 88.3%, good knowledge at 73.4%, and authoritarian parenting at 56.4%. The bivariate results showed no relationship between adolescent knowledge and sexual behavior, namely p value: 0.604 (OR: 1.040), there was a relationship between parental parenting and adolescent sexual behavior with the result p value: 0.023 (OR: 8.444). It is hoped that the school will collaborate with the local Community Health Center to provide regular assistance to SMAN 15 Jakarta students to increase their knowledge, especially regarding reproductive health. Keywords: adolescent sexual behavior, knowledge, parenting patterns